Sexually Transmitted Infection Prevalence among Homeless Adults in the United States: A Systematic Literature Review - Williams, Samantha P. (Sex Transm Dis, 2018)
BACKGROUND: Homelessness significantly affects health and well-being. Homeless adults often experience co-occurring and debilitating physical, psychological, and social conditions. These determinants are associated with disproportionate rates of infectious disease among homeless adults, including tuberculosis, HIV, and hepatitis. Less is known about sexually transmitted infection (STI) prevalence among homeless adults. METHODS: We systematically searched 3 databases and reviewed the 2000–2016 literature on STI prevalence among homeless adults in the United States. We found 59 articles of US studies on STIs that included homeless adults. Of the 59 articles, 8 met the inclusion criteria of US-based, English-language, peer-reviewed articles, published in 2000 to 2016, with homeless adults in the sample. Descriptive and qualitative analyses were used to report STI prevalence rates and associated risk factors. RESULTS: Overall, STI prevalence ranged from 2.1% to 52.5%. A composite STI prevalence was most often reported (n = 7), with rates ranging from 7.3% to 39.9%. Reported prevalence of chlamydia/gonorrhea (7.8%) was highest among younger homeless adult women. Highest reported prevalence was hepatitis C (52.5%) among older homeless men. Intimate partner violence, injection and noninjection substance use, incarceration history, and homelessness severity are associated with higher STI prevalence. CONCLUSIONS: Homeless adults are a vulnerable population. Factors found to be associated with sexual risk were concurrently associated with housing instability and homelessness severity. Addressing STI prevention needs of homeless adults can be enhanced by integrating sexual health, and other health services where homeless adults seek or receive housing and other support services.